Reconstruction of Old Pavements Based on Resonant Rubblization Technology: A Review of Technological Progress, Engineering Applications, and Intelligent Development - Sibo Ding; Dehuan Sun; Yongtao Hu; Shuang Lu; Zedong Qiu; Shuo Zhang; Lei Wang; Shaowei Jiang; Tao Han; Yingli Gao (Buildings, 2025)
With the continuous expansion of highway networks and rapid advancements in the transportation industry, the need for highway maintenance and reconstruction has become increasingly urgent. Resonant rubblization technology generates an interlocking structure within the pavement layer by producing diagonal cracks at angles of 35–40°, thereby significantly enhancing load-bearing capacity and structural stability. As a result, this technique offers substantial benefits, including a marked reduction in reflective cracking, efficient reuse of existing concrete slabs (with a utilization rate exceeding 85%), reduced construction costs (by 15–30% compared to conventional methods), and faster construction speeds—up to 7000 square yards per day. Consequently, resonant rubblization has emerged as a key method for rehabilitating aging cement concrete pavements. Building on this foundation, this paper reviews the fundamental principles of resonant rubblization technology by synthesizing global research findings and engineering case studies. It provides a comprehensive analysis of the historical development, equipment design, construction principles, and practical application outcomes of resonant rubblization, with particular attention to its effects on pavement structure, load-bearing capacity, and long-term stability. Future research should focus on developing more realistic subgrade models, improving evaluation methods for post-rubblization pavement performance, and advancing the intelligentization of resonant equipment. The ultimate goal is to enhance the quality of road maintenance and repair, ensure road safety, and promote the development of long-life, sustainable road infrastructure through the continued advancement and application of resonant rubblization technology.